Work related health problems of female workers engaged in Cashew processing Industries- a cross-sectional study from Kollam district, Kerala, southern India - Nelson, Vincy; PS, Rakesh; Simon, Sony; Hashim, Anwar; Usman, Anzeena; Rassia, Anzil A (Indian Journal of Community Health, 2016)
Background: India accounted for one third of the global export market for cashew kernels. Unhealthy sitting posture, working near furnaces and contact with the cashew nut shell liquid may make the workers in the cashew sector vulnerable to many health issues Aims & Objectives: To identify the health related problems among female workers of cashew processing industries in Kollam district, southern Kerala, Setting and Design: A cross sectional study was conducted in selected cashew units of Kollam, Kerala. Material & Methods: An interviewer administered and structured questionnaire was used to collect health related issues from 301 female cashew processing workers. Statistical analysis: Descriptive statistics using frequencies was done and chi square test was used to detect difference between proportions. Results: Low back pain was the predominant problem (48.8%) followed by hand and wrist pain (46.6%), knee pain (37.8%) and neck pain (32.5%). Among the workers engaged in roasting, 86.6% had experienced a burn (p < 0.001). Workers engaged in roasting (53.3%) and shelling (43.7%) had blackish staining of their palms and fingers. Conclusion: Health related issues pertaining to musculoskeletal system, respiratory system, and skin conditions are highly prevalent among women engaged in cashew processing industry. A comprehensive programme to prevent health related issues may be considered to promote health of women engaged in cashew processing industries